Comparative analysis of gas release from biphasic lithium ceramics pebble beds of various pebbles sizes and content under neutron irradiation conditions - Timur Kulsartov; Zhanna Zaurbekova; Regina Knitter; Inesh Kenzhina; Yevgen Chikhray; Asset Shaimerdenov; Saulet Askerbekov; Gunta Kizane; Alexandr Yelishenkov; Timur Zholdybayev (Nuclear Materials and Energy, 2024)
This paper presents the results of 4 reactor campaigns on the irradiation of biphasic lithium ceramics containing different ratios of lithium orthosilicate (LOS) and lithium metatitanate (LMT) components (25 and 35 mol% LMT in LOS). The size distribution of pebbles in pebble beds was 250–1250 μm and 500–710 μm, respectively. The studies were carried out sequentially with each type of ceramics. In experiments carried out using the vacuum extraction method, the composition of gases released from lithium ceramic samples was registered in in-situ mode. The absence of purge gas during the experiments minimized the possibility of T2O and HTO formation, significantly simplifying processing of the results and providing more opportunities for results analysis. The main goal of the present paper was to identify the general patterns of the release of gases with mass numbers M2 (H2), M4 (He + HT), M6 (T2) and M18 (H2O) from ceramic samples throughout the entire irradiation experiment in 4 campaigns. Release trends of main gases with mass numbers M2, M4, M6 and M18 for all four campaigns are presented and their comparative analysis was performed. The average partial pressure of tritium release in the form of T2 and HT molecules for all campaigns was determined as 5.8 × 10-7 Torr. The dependences of formation rates of helium release peaks on the irradiation time were plotted. The nature of peak emissions does not have a monotonic relationship; upon irradiation, both an increase in the frequency of peaks and a decrease in it are observed. During irradiation, the process of peak helium release does not stop.The simulation was carried out by the finite element method, assuming that tritium release from the sample is determined by diffusion and desorption processes from the sample surface. The experimental curves are satisfactorily described by a number of sets of desorption and diffusion parameters. One way or another they lie in the range of specified values. The Arrhenius dependences of the effective diffusion coefficient and desorption coefficient obtained for lithium ceramics 35 LMT are equal to:D=5,2×10-11m2sexp-21kJmoleRT,K=1.21×10-4m2sexp-64kJmoleRT.The values of the effective diffusion coefficient and tritium desorption coefficient in 25 LMT ceramics were 15 and 20% lower than in 35 LMT ceramics.